Current state and forecast of development of the Russian civil aviation market ("Journal "U". Economy. Management. Finance.", 2023)
The article analyzes the prospects for the development of the Russian aviation industry in the context of international economic sanctions. The current situation in Russian civil aviation is briefly analyzed. The problems of aviation development and ways to solve them in the context of existing technologies, as well as business constraints are considered. The relevance of this topic is due to the role of the aviation industry in the formation of the scientific and economic potential of the country. The results of the analysis allow us to assess and predict the future existence of the country's aviation industry.
Keywords: civil aviation; Russian market; development; sanctions; development forecast; airspace